2011
DOI: 10.1158/1940-6207.capr-11-0107
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-inflammatory Drug Use and Risk of Adenomatous and Hyperplastic Polyps

Abstract: Adenomatous polyps are known precursor lesions for colorectal cancer and some hyperplastic polyps also have malignant potential. The use of aspirin and non-steroidal anti-inflammatory drugs (NSAIDS) is associated with a reduced risk of adenomatous polyps; however, less evidence exists regarding NSAID use and hyperplastic polyp risk. We conducted a colonoscopy-based case-control study including 2028 polyp cases (1,529 adenomatous and 499 hyperplastic) and 3,431 polyp-free controls. Multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…49 Furthermore, the United Kingdom Colorectal Adenoma Prevention (UKCAP) study showed that aspirin decreased risk of adenoma (relative risk, 0.79; 95% CI, 0.63-0.99) and advanced adenoma (relative risk, 0.63; 95% CI, 0.43-0.91). 50 Similar results were observed in other studies 32,51 and are supported by a meta-analysis. 52 Data from the Nurses' Health Study showed the greatest reduction in adenoma risk for participants who took 14 or more tablets of aspirin per week (relative risk, 0.49; 95% CI, 0.36-0.65).…”
Section: Aspirinsupporting
confidence: 87%
“…49 Furthermore, the United Kingdom Colorectal Adenoma Prevention (UKCAP) study showed that aspirin decreased risk of adenoma (relative risk, 0.79; 95% CI, 0.63-0.99) and advanced adenoma (relative risk, 0.63; 95% CI, 0.43-0.91). 50 Similar results were observed in other studies 32,51 and are supported by a meta-analysis. 52 Data from the Nurses' Health Study showed the greatest reduction in adenoma risk for participants who took 14 or more tablets of aspirin per week (relative risk, 0.49; 95% CI, 0.36-0.65).…”
Section: Aspirinsupporting
confidence: 87%
“…NSAIDs and aspirin use may be an approach for colorectal neoplasia prevention; however, very little is known regarding NSAIDs and their association with SSP risk [10,13,24,25]. A previous study of serrated polyps found an inverse association between aspirin use and serrated polyp risk which was particularly strong for proximal lesions [10].…”
Section: Discussionmentioning
confidence: 99%
“…Twelve articles summarising results from one RCT 25 and 11 observational studies 29,30,40,42,44,45,47,50,54,61,62 investigated the risk of SP for individuals taking NSAIDs and/or aspirin, two of which also reported SSA/P risk 29,30 , as outlined in Supplementary Table 1(e). The RCT (which was not included in meta-analyses due to the different study design) demonstrated a significant protective association for right-sided, but not left-sided, SP when taking 81mg or 325mg of aspirin compared with placebo 25 .…”
Section: Medicationsmentioning
confidence: 99%